2000
DOI: 10.1038/sj.jea.7500091
|View full text |Cite
|
Sign up to set email alerts
|

The spatial and temporal variation of particulate matter within the home

Abstract: Numerous epidemiological studies have found associations between ambient particulate matter and adverse health outcomes. The importance of indoor particles has also been recognised since people spend an average of 90% of their time indoors. In order to better understand exposure to particles this study was carried out to provide data on the characteristics of airborne particulate matter found inside homes in the UK. Forty -eight -h measurements were taken at 10 houses during the summer of 1999. Particulate mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 5 publications
0
24
2
Order By: Relevance
“…It has been previously reported that people tend to stay for longer periods indoors than outdoors (GB Parliament House of Commons Environment Committee, 1991;Wigzell et al, 2000). As expected, outdoor microenvironments had higher concentrations than indoor, even though the former represented only the 22% of the overall sample measurements.…”
Section: Microenvironment and Geographical Location Exposure Concentrmentioning
confidence: 61%
See 1 more Smart Citation
“…It has been previously reported that people tend to stay for longer periods indoors than outdoors (GB Parliament House of Commons Environment Committee, 1991;Wigzell et al, 2000). As expected, outdoor microenvironments had higher concentrations than indoor, even though the former represented only the 22% of the overall sample measurements.…”
Section: Microenvironment and Geographical Location Exposure Concentrmentioning
confidence: 61%
“…Until recently, most epidemiological studies have been conducted using fixed monitors either in an indoor and/or in outdoor microenvironment (Borja-Aburto et al, 1997;Chen et al, 1999;Gold et al, 1999). These devices yield only an average particulate matter concentration and do not reflect the fluctuations in particulate levels over the sampling period, and therefore, a less accurate measurement of PM personal exposure is obtained in comparison to light-scattering nephelometers that provide a more accurate and precise resolution of particulate matter measurements (Quintana et al, 2000;Wigzell et al, 2000). A published work that evaluated the performance of Personal DataRAM (2000) (pDRs) and Radiance nephelometer against measurements from both Harvard impactors (HI 2.5 ) and Harvard personal environmental monitors (HPEM 2.5 ) for PM 2.5 indoor, outdoor and personal settings showed that pDRs measurement of PM 2.5 could systematically overestimate the HPEM 2.5 measurements by approximately 27% (Liu et al, 2002).…”
Section: Study Considerations and Limitationsmentioning
confidence: 99%
“…In both cases, the case was at arm's length and the inlet thus close to breathing zone. It is unlikely that there would have been large concentration gradients between breathing zone and the inlet, as PM 2.5 is quite homogeneously distributed because of its small size ( Wigzell et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Particle concentrations were elevated by burning two sticks of incense and shaking a used vacuum cleaner bag, and the door was closed. The subsequent decay of particles to background levels was monitored concurrently at 1-min intervals for a period of approximately 2 h. Using the colocation data, one OPC was calibrated relative to the other as a reference using linear regressions of the concentrations of each of the six particle bins measured with each counter, similar to the method in Wigzell et al (2000).…”
Section: Upstream-downstream Removal Methodsmentioning
confidence: 99%